ANALISIS SITUASI FILARIASIS LIMFATIK DI KELURAHAN SIMBANG KULON, KECAMATAN BUARAN, KABUPATEN PEKALONGAN - Tri Wijayanti (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2009)
Lymphatic filariasis an infection disease caused by parasitic nematode that transmitted by various mosquito spesies and affect to damage of lymphatic system in human body. This disease identified as permanent handicap. Pekalongan district is lymphatic filariasis endemic area in Central Java Province. Distribution of chronic/clinic filariasis cases have been found occure in 6 sub districts e.i (Siwalan sub district, Kesesi, Kajen, Buaran and Paninggaran). Chronic filariasis cases in Buaran Public Health Center (Puskesmas) area on 2007 were 4 cases, 3 cases are reported in Kelurahan Simbang Kulon.That's describe tha there is filariasis transmission in Kelurahan Simbang Kulon. The aim of this research were to know microfilaria rate ( Mf rate), number of microfilaria every slide and distribution of filariasis case based on age and gender in Kelurahan Simbang Kulon, Pekalongan.This research an observational and descriptive study on secondary data from Pekalongan Health District Agency and Loka Litbang P2B2 Banjarnegara.Result of this research showed Mf rate in Kelurahan Simbang Kulon at 2007 was 3,91% in 2008, 2,65%. In 2007, mostly was found in filariasis patients of 13 years old ( 13 Mf), in 2008 after MDA (Mass Drug Administration), mostly number microfilaria found in patient 65 years old (14 Mf). More than 70% of cases found in men of adult age group.